2017
DOI: 10.1016/j.micpath.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Heidelberg: Genetic profile of its antimicrobial resistance related to extended spectrum β-lactamases (ESBLs)

Abstract: The objective of this study was to evaluate the phenotypic and genotypic profile of antimicrobial susceptibility and the possible involvement of extended spectrum beta-lactamases (ESBLs) in the resistance profile of Salmonella Heidelberg (SH) isolated from chicken meat. We used 18 SH isolates from chicken meat produced in 2013 in the state of Paraná, Southern Brazil. The isolates were submitted to disk-diffusion tests and from these results it was possible to determine the number of isolates considered multire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…The gene bla TEM-1, is reported to be the most widely distributed of the β-lactamase genes worldwide [ 52 ] and is mainly known to be spread by plasmids. Not much information is available on the occurrence of beta-lactamase encoding genes in isolates from poultry in Uganda, but similar results have been reported in studies elsewhere [ 69 , 70 , 71 ]. Carriage of the bla TEM-1 gene is a threat to the potency of β-lactam antibiotics and in the case of Uganda, ampicillin is still widely used in human and veterinary medicine.…”
Section: Discussionsupporting
confidence: 74%
“…The gene bla TEM-1, is reported to be the most widely distributed of the β-lactamase genes worldwide [ 52 ] and is mainly known to be spread by plasmids. Not much information is available on the occurrence of beta-lactamase encoding genes in isolates from poultry in Uganda, but similar results have been reported in studies elsewhere [ 69 , 70 , 71 ]. Carriage of the bla TEM-1 gene is a threat to the potency of β-lactam antibiotics and in the case of Uganda, ampicillin is still widely used in human and veterinary medicine.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, the isolates show high prevalence of resistance to nalidixic acid and ciprofloxacin (FQ), a fact also observed by other authors in isolates from poultry (Casas et al, 2016;van den Berg et al, 2019). Similarly, an increasing number of isolates have been characterized as MDR to many antimicrobials by several authors (Giuriatti et al, 2017). Resistance to TGCs and resistance to FQ are usually associated, and these antibiotics are the first choice for the treatment of human salmonellosis (Wen et al, 2017), which represents a serious threat for the public health.…”
Section: Discussionmentioning
confidence: 78%
“…51,67 The prevalence of bla CMY-2 in the current study was similar to a previous study which reported a rate of 38.88%. 75 The high prevalence of beta-lactam degrading genetic determinants in this study is of concern because extended beta-lactams such as ceftriaxone are the drug of choice for salmonellosis treatment in children and pregnant women. 42 The prevalence of tetC, dfrA7 and bla TEM-1 genes was significantly (p<0.05) associated with farm location ( Table 5).…”
Section: Discussionmentioning
confidence: 89%